Attitudes of special education teachers towards using technology in inclusive classrooms: a mixed-methods study - Mohamed, Ahmed Hassan Hemdan (Journal of Research in Special Educational Needs, 2018)
The purpose of this mixed-methods study was to explore special education teachers’ attitudes towards using technology in inclusive classrooms in Oman. The sample consisted of 428 special education teachers working in Omani public schools (250 teachers of students with learning disabilities (LD), 90 teachers of students with intellectual disability and 88 teachers of students with hearing impairment). Participants responded to the attitudes towards computers questionnaire. For the qualitative section of this study, three semi-structured group interviews were conducted with a group of special education teachers: 15 teachers of students with hearing impairment, 15 teachers of students with intellectual disabilities and 15 teachers of students with LD). Also, the teachers responded to a survey of educational technology which encompassed seven questions about computer technology. Results of the study indicated that the special education teachers’ attitudes towards using computers were generally positive. The most notable positive attitudes were in the following subscales: special education considerations, staff development considerations, computers use in society, and computers and quality of instruction issues. The analysis of variance results showed that experience and type of disability did not have a significant effect on teachers’ attitudes towards technology.
KerkoCite.ItemAlsoKnownAs: 10.1111/1471-3802.12411 2339240:VM328LPK 2405685:7J6H34I4
Keywords: Attitudes; hard of hearing; inclusive education; intellectual disability; learning disabilities; technology

Who’s teaching math to our most needy students? A descriptive study - Rosas, Clarissa; Campbell, Lisa (Teacher Education and Special Education, 2010)
The No Child Left Behind Act (NCLB) mandates that every classroom be staffed with a “highly qualified teacher.” Research supports that teachers’ content knowledge affects student achievement. However, the special education population continues to be taught by teachers who do not have the content area background they teach. In addition, accountability reports indicate that the special education population did not meet the adequate yearly progress in reading and mathematics as required under NCLB. The purpose of this study is to determine the mathematical background, beliefs, and perceptions of future intervention specialists. Results of this study indicate a disconnect between the participants’ beliefs and perceptions of their ability to provide math instruction and their limited mathematical background as measured by mathematical courses completed at the undergraduate level and by the Ohio Achievement Test—Practice Eighth Grade Mathematics.
Publisher: SAGE Publications Inc KerkoCite.ItemAlsoKnownAs: 10.1177/0888406409357537 2339240:7V955V2Q 2405685:YHKAEKGD
Keywords: math; special education; standardized tests; teacher’s perception

5 Ways EdTech Helps Students With Special Needs in the Classroom - Davis, Chris (ViewSonic Library, 2019)
EdTech helps students with special needs to engage with learning better than ever before. Find out how to implement EdTech as assistive technology.
Library Catalog: www.viewsonic.com Section: Education KerkoCite.ItemAlsoKnownAs: 2339240:L69ICGF3 2405685:SCWN8NNM SCWN8NNM

Teachers' Attitude and Competence in the Use of Assistive Technologies in Special Needs Schools - Onivehu, Adams Ogirima; Ohawuiro, Onyiyeche Emilia; Oyeniran, Bunmi Juliana (Acta Didactica Napocensia, 2017)
This study examined teachers' attitude and competence in the use of assistive technologies in special needs schools. The descriptive survey method was employed for the study among 100 teachers who were drawn using purposive sampling technique from special needs schools in Osun State, Nigeria. Six research questions were generated while four hypotheses were tested at 0.05 level of significance. A researcher-constructed questionnaire tagged "Teachers' Attitude and Competence in the Use of Assistive Technology Questionnaire" ("TACUATQ") was used for data collection. The instrument was administered on 20 selected teachers outside the sample location through test-retest method; it yielded a reliability coefficient of 0.85 through Pearson Product Moment Correlation statistics. Data were analysed with percentage, mean and rank order, t-test and ANOVA statistical tools. The findings revealed that teachers have a positive attitude towards the use of assistive technologies. However, teachers were not competent in the use of assistive technologies. Gender and teaching experience did not influence teachers' attitude and competence in the use of assistive technologies. It was recommended among other things that teachers should be trained and re-trained on the use of assistive technology for students with speech disorders, visual impairments, hearing impairments, physical impairments and emotional and behavioural disorders.
Publisher: Babes-Bolyai University KerkoCite.ItemAlsoKnownAs: 10.24193/adn.10.4.3 2339240:FDGRYPVG 2405685:TUG39XRX
Keywords: Assistive Technology; Elementary Secondary Education; Foreign Countries; Gender Differences; Questionnaires; Special Needs Students; Special Schools; Teacher Attitudes; Teacher Competencies; Teacher Surveys; Teaching Experience

International distance learning in special education: a program evaluation of a US-Ecuador collaboration - McPherson, Rebekah (University of North Texas, 2010)
The internationalization of distance learning in special education is at a pivotal point in expansion. Even with concerted efforts through traditional means to increase the supply of special educators, shortages persist; therefore, teacher preparation programs are turning to online education. This dissertation study was a formative program evaluation of a bilingual, two-course sequence within a web-based special education master’s program offered at the University of North Texas (UNT), in Denton, Texas, and at the Universidad Casa Grande (UCG) in Guayaquil, Ecuador. The research design was based on the unfolding model of program evaluation, and it included mixed-methods of data collection. The model focused attention on (1) scientific evidence, (2) cost-benefit differential, (3) underlying values, and, (4) unintended consequences. Data came from archived documents as well as six semi-structured interviews with stakeholders and survey data from 23 student participants. The findings for the general-orientation course, Special Education Programs and Practices, revealed mixed results concerning multicultural awareness on the part of student participants. However, it seemed to have influenced their lesson design and made a difference in other areas. Some multicultural awareness concepts frequented the discussion board. The specialized course, Assistive Technology, which had more frequent communication between UNT and UCG on the discussion board, suggested larger increases in students’ multicultural awareness. With respect to both courses, the stakeholders recommended that the structure be strengthened for non-bilingual instructors and students to be able to communicate more freely.
ISBN: 978-1-124-34768-4 Publication Title: ProQuest Dissertations and Theses 3436539 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/818457302?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2339240:RU2VEJFD 2405685:37N9VRF7 2405685:PGTN56VE 2534378:3DJPRT2X 2534378:ERVGUH59 2534378:NSJ46FI4
Keywords: 0529:Special education; 0530:Teacher education; 0710:Educational technology; Curriculum Design; Data Collection; Disabilities; Distance Education; Distance learning; ERIC; Resources in Education (RIE); Ecuador; Education; Educational Technology; Educational technology; Evidence; Foreign Countries; Graduate Students; Higher Education; International collaboration; Interviews; Masters Programs; Online instruction; Online learning; Program Evaluation; Program evaluation; Research Design; Special Education; Special education; Surveys; Teacher education; Texas; Unfolding model; United States; __:import:01; __:match:final; __:matched; __:study_id:2098174; __finaldtb

Special Needs Education: Country Data 2012 (European Agency for Development in Special Needs Education, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:2R6EC87G 2405685:A7NTS6EN

Developing Interactive Multimedia Flood Prevention Education (FPE) on Disaster Risk Reduction Learning for Students with Hearing Impairment in Special School - Robiansyah, Iva Evry; Mudjito; Yuliyati; Atiqoh (2019 5th International Conference on Education and Technology (ICET), 2019)
This study aims to describe the practicality of interactive multimedia flood prevention education (FPE) in improving the understanding of flood disaster risk reduction (DRR) and describing the understanding of flood disaster management learning for students with hearing impairment. This development research used the design of media development stages according to Luther with the development of media applications based on 5 stages namely: concept, design, material collecting, assembly, testing. Data were collected from through observation and tests. The result of this development product is interactive multimedia flood prevention education (FPE) to tackle flood risk among students with hearing impairment. Based on research on the development of interactive multimedia flood prevention education (FPE) to reduce the risk of flooding for students with hearing impairment in Special School Pasuruan City, it can be concluded that the results of the questionnaire show that the students' responses were very positive in using multimedia FPE in reducing the risk of flood disasters.
0 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1109/ICET48172.2019.8987227 2339240:W2CBCAC5 2405685:8HMZKBXQ
Keywords: disaster risk reduction; flood prevention education; interactive multimedia; special school; students with hearing impairment; ⛔ No INSPIRE recid found

Interactive Apps Promote Learning of Basic Mathematics in Children With Special Educational Needs and Disabilities - Pitchford, Nicola J.; Kamchedzera, Elizabeth; Hubber, Paula J.; Chigeda, Antonie L. (Frontiers in Psychology, 2018)
Interactive apps delivered on touch-screen tablets can be effective at supporting the acquisition of basic skills in mainstream primary school children. This technology may also be beneficial for children with Special Educational Needs and Disabilities (SEND) as it can promote high levels of engagement with the learning task and an inclusive learning environment. However, few studies have measured extent of learning for SEND pupils when using interactive apps, so it has yet to be determined if this technology is effective at raising attainment for these pupils. We report the first observational study of a group of 33 pupils with SEND from two primary schools in Malawi that are implementing a new digital technology intervention which uses touch-screen tablets to deliver interactive apps designed to teach basic mathematical skills. The apps contain topics that align to the national curriculum. To assess learning gains, rate of progress (minutes per topic) for each pupil was determined by calculating the average time taken to complete a topic. Progress rate was then correlated with teacher ratings of extent of disability and independent ratings of pupil engagement with the apps. Results showed SEND pupils could interact with the apps and all pupils passed at least one topic. Average progress rate for SEND pupils was twice as long as mainstream peers. Stepwise regression revealed extent of disability significantly predicted progress rate. Further exploratory correlations revealed pupils with moderate to severe difficulties with hearing and/or language made slower progress through the apps than those with greater functionality in these two domains because the use of verbal instructions within the apps limited their capacity to learn. This original quantitative analysis demonstrates that interactive apps can raise learning standards in pupils with SEND but may have limited utility for pupils with severe difficulties. Software modifications are needed to address specific areas of difficulty preventing pupils from progressing.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2018.00262 2339240:DUN6JGMK 2339240:UQ8D45IR 2405685:7WAJ6HEZ 2405685:JSQPF627
Keywords: Interactive apps; Mathematics; Special educational needs and disabilities; primary school; tablet technology

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Publisher: Routledge _eprint: https://doi.org/10.1080/14623943.2017.1361921 KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2339240:UPNEHQVJ 2405685:8CQU3AHD
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Enhancing peer interaction: an aspect of a high-quality learning environment in Finnish early childhood special education - Syrjämäki, Marja; Sajaniemi, Nina; Suhonen, Eira; Alijoki, Alisa; Nislin, Mari (European Journal of Special Needs Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1080/08856257.2016.1240342 2339240:KX7AIXX6 2405685:UBAETY3T

Inclusive and special education approaches in developing countries - Price, Roz (Institute of Development Studies, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7AUCVAJC 2405685:ICKQU7NT
Keywords: ⛔ No DOI found

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics: - Kiboss, Joel Kipkemboi (Journal of Educational Computing Research, 2012)
Achievement in mathematics is an issue of great concern not only to students and parents but also to employers and researchers in Kenya. This is because the Ken...
Sage CA: Los Angeles, CA shortDOI: 10/ggdtp3 KerkoCite.ItemAlsoKnownAs: 10.2190/EC.46.1.b 10.2190/ec.46.1.b 10/ggdtp3 2339240:E2A49LQS 2339240:SRIBPMIE 2405685:TBHFERAU 2405685:Z3BJFVR2

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Publisher: IISTE KerkoCite.ItemAlsoKnownAs: 2339240:VXMFTYG8 2405685:8FZZT8ZT
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

Facilitators and barriers of assistive technology and learning environment for children with special needs - Lersilp, Suchitporn; Putthinoi, Supawadee; Lersilp, Theeratorn (Occupational Therapy International, 2018)
The purpose of this research was to study the facilitators and barriers of assistive technology (AT) and the learning environment for children with special needs in special education schools in Chiang Mai, Thailand. The informants were one hundred and sixteen children with special needs, who studied in nursery to Grade 12, or with their caregivers. The instrument was a questionnaire applied by the International Classification of Functioning, Disability and Health (ICF) and examined for content validity by five specialists. The results in terms of AT showed that a majority of children with physical disability needed it for mobility and use of school buildings and those with hearing disability for communication. However, most of the children did not need to use AT for culture, recreation, or sports, while many considered it as a facilitator for education. In terms of the learning environment, most characteristics of the physical environment were facilitators for children with special needs, as were those of the social environment for all groups of such children. The results of this study were useful in providing information for AT and design of a learning environment relating to the varied characteristics of children with special needs in special education schools.
13 citations (Crossref) [2024-02-28] Publisher: Hindawi KerkoCite.ItemAlsoKnownAs: 10.1155/2018/3705946 2339240:MNJXAI5P 2405685:DGKJ8CRQ
Keywords: ⛔ No INSPIRE recid found

Facilitators and Barriers of Assistive Technology and Learning Environment for Children with Special Needs - Lersilp, Suchitporn; Putthinoi, Supawadee; Lersilp, Theeratorn; Mackenzie, Lynette (Occupational Therapy International, 2018)
The purpose of this research was to study the facilitators and barriers of assistive technology (AT) and the learning environment for children with special needs in special education schools in Chiang Mai, Thailand. The informants were one hundred and sixteen children with special needs, who studied in nursery to Grade 12, or with their caregivers. The instrument was a questionnaire applied by the International Classification of Functioning, Disability and Health (ICF) and examined for content validity by five specialists. The results in terms of AT showed that a majority of children with physical disability needed it for mobility and use of school buildings and those with hearing disability for communication. However, most of the children did not need to use AT for culture, recreation, or sports, while many considered it as a facilitator for education. In terms of the learning environment, most characteristics of the physical environment were facilitators for children with special needs, as were those of the social environment for all groups of such children. The results of this study were useful in providing information for AT and design of a learning environment relating to the varied characteristics of children with special needs in special education schools.
KerkoCite.ItemAlsoKnownAs: 10.1155/2018/3705946 2339240:IP8YALEF 2405685:RQFMF9HT

Education and Disability in the Global South: New Perspectives from Africa and Asia - Singal, Nidhi; Lynch, Paul; Johansson, Shruti Taneja (Bloomsbury Publishing, 2018)
Education and Disability in the Global South brings together new and established researchers from a variety of disciplines to explore the complexities and dilemmas encountered in providing education to children and young people with disabilities in countries in South Asia and Africa. Applying a range of methodological, theoretical and conceptual frameworks across different levels of education systems, from pre-school to higher education, the contributors examine not just the barriers but also the opportunities within the educational systems, in order to make strong policy recommendations. Together, the chapters offer a comprehensive overview of a range of issues, including a nuanced appreciation of the tensions between the local and global in relation to key developments in the field, critiquing a globalized notion of inclusive education, as well as proposing new methodological advancements in taking the research agenda forward. Empirical insights are captured not just from the perspectives of educators but also through engaging with children and young people with disabilities, who are uniquely powerful in providing insights for future developments.
Google-Books-ID: get1DwAAQBAJ KerkoCite.ItemAlsoKnownAs: 2339240:DZELW96T 2405685:9MZNXBIX
Keywords: Education / Educational Policy & Reform / General; Education / Inclusive Education; Education / Special Education / General

Survey of the Use of Assistive Technology in Schools in Nigeria - Ajuwon, Paul M.; Chitiyo, George (Journal of the International Association of Special Education, 2015)
In this study, the researchers explored the state of the use of assistive technology (AT) in Nigeria through a survey of 165 special educators. The underlying structure of the respondents' perceptions, and their challenges and barriers to the use of AT, were examined. Among other findings, the largest proportion of students using AT are those with deafness or hearing impairment (53.3%), followed by those with a learning disability (40%). Training in the use of AT lags behind, with most professionals having received little or no training in the use of AT. The lack of appropriate AT devices and services in classrooms, and irregular electricity to operate available devices, were frequently cited as the biggest challenges regarding AT. Correlations between students' conditions and factors of teachers' perceptions suggested the need to make AT available for students with certain conditions, as well as the need for effective training for teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:2B5LKGDA 2405685:XS664IV7
Keywords: Access to Computers; Assistive Technology; Barriers; Computer Uses in Education; Deafness; Disabilities; Educational Technology; Energy; Faculty Development; Foreign Countries; Hearing Impairments; Learning Disabilities; Likert Scales; Special Education Teachers; Statistical Analysis; Teacher Competencies; Teacher Surveys; Technological Literacy; Training; ⛔ No DOI found

Why people use and don’t use technologies: Introduction to the special issue on assistive technologies for cognition/cognitive support technologies - Scherer, Marcia J.; Federici, Stefano (NeuroRehabilitation, 2015)
This special issue focuses on assistive technologies for cognition/cognitive support technologies as well as the ways in which individuals are assessed and trained in their use. We provide eleven diverse articles that give information on products, why they are used and not used, and best professional practices in service provision. Our goal is to highlight a broad topic that has received limited research investigation and offer an insight into how different countries and programs are promoting access to and use of assistive technologies for cognition/cognitive support technologies
Publisher: IOS Press KerkoCite.ItemAlsoKnownAs: 10.3233/NRE-151264 2339240:RXAAUBQE 2405685:AKMUZPJ4
Keywords: Assistive technology devices; Matching Person and Technology Model; abandonment; assistive technology services; brain injury; cognitive support technologies; nonuse

Variables affecting teachers' attitudes towards inclusive education in Bangladesh - Ahmmed, Masud; Sharma, Umesh; Deppeler, Joanne (Journal of Research in Special Educational Needs, 2012)
Inclusive education is a worldwide reform strategy intended to include students with different abilities in mainstream regular schools. Evidence from previous research shows that success in implementing effective inclusive teaching practices in the school is contingent on teachers' positive attitudes towards inclusive education. This study was conducted in the context of primary education in Bangladesh aiming to examine variables influencing teachers' attitudes towards inclusion of students with disabilities in regular classrooms. Data for the study was collected from 738 teachers working in 293 government primary schools in Bangladesh. The results indicated that perceived school support for inclusive teaching practices and a range of demographic variables including previous success in teaching students with disabilities and contact with a student with a disability were associated with more positive attitudes of the teachers towards the inclusive education. The results are discussed with possible implications for educators, policy-makers and international organisations working on the implementation of inclusive education. © 2012 The Authors. Journal of Research in Special Educational Needs
KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2011.01226.x 2339240:EJGQITXV 2405685:KJHBE65X

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 2339240:9SHHNJCH 2405685:WQ7ZLZVW
Keywords: ___working_potential_duplicate

Inclusive education in an international school: A case study from Hong Kong - Chan, T.; Yuen, Mantak (International Journal of Special Education, 2015)
This case study provides an overview of current policy, practices and problems concerning inclusion in one international secondary school in Hong Kong. A total of 13 interviews were conducted with the school management team, teachers, students and parents, supplemented by 12 classroom observations and two ‘student-shadowing’ exercises. Findings suggest that the school has been reasonably successful in raising teachers’ awareness of inclusive education principles, creating a whole-school culture of inclusiveness, and forming a partnership with parents. However, the commitment of individual teachers to implementation of inclusive practices in their own classrooms varies. Some teachers are not adaptive enough in their teaching approach, and have difficulties differentiating instruction and learning activities. Improvements are also needed in the way that teachers work with their education assistants (classroom aides). Implications for improvement are discussed. © 2015, International Journal of Special Education. All rights reserved.
KerkoCite.ItemAlsoKnownAs: 2339240:G6HTWKIA 2405685:5VS97KU6

Inclusive education and students without special educational needs - Ruijs, Nienke; Van der Veen, Ineke; Peetsma, Thea (Educational Research, 2010)
Background: In the debate on inclusive education, students without special educational needs (SEN) are an important topic. However, there is a lot unknown about differences between these typical students in inclusive and non-inclusive classes. For example, the neutral results that are often found in earlier research could be caused by positive effects for some students, and negative effects for others.Purpose: This study investigated whether there is a relation between inclusive education and the academic achievement and socio-emotional functioning of typical students, and, more importantly, whether inclusive education affects the achievement and socio-emotional functioning of more and less intelligent typical students differently. Furthermore, we investigated whether differences occur by type of SEN of the included students. Here, we made a distinction between students with behavioural, cognitive and other problems.Sample: A representative sample of 27,745 students without SEN in Dutch primary education from a large cohort study in the Netherlands was used.Design and methods: Language and arithmetic tests were used to assess academic achievement. For socio-emotional functioning, both teacher and student questionnaires were used. A non-verbal IQ test was used to assess student intelligence. Based on the number of students with diagnosed SEN, the students without SEN were divided into several groups: typical students with no, a few and more than a few students with (certain types of) SEN in their class. Multi-level regression analyses were used to compare these groups.Results: For academic achievement, no differences were found between students without SEN in inclusive and non-inclusive classes. In this, we found no differences between intelligent and less intelligent typical students. For socio-emotional functioning, some differences were found, but the practical importance of these differences is unclear, since the effect sizes were small. The functioning of typical students does not meaningfully differ by type of SEN of the included students.Conclusions: The findings of this study are interesting in the light of the ongoing inclusion debate. Arguments against inclusive education often concern an assumed adverse effect on typical students. As in this study, hardly any differences were found between typical students in inclusive and non-inclusive primary school classes, this research strengthens the scientific evidence in support of inclusive education.
51 citations (Crossref) [2024-04-17] KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2010.524749 2339240:SSS5GMEL 2405685:GTTYFAFH
Keywords: ⛔ No INSPIRE recid found

An animated dictionary for hearing-impaired students in Thailand - Wicha, Santichai; Sharp, Bernadette; Sureephong, Pradorn; Chakpitak, Nopasit; Atkins, Anthony (Journal of Research in Special Educational Needs, 2012)
As English increasingly becomes the international language, many ministerial and educational organisations have identified the need to improve the competence of Thai students in speaking English. While there is significant research devoted to developing software tools to support the teaching of English as a second language, they are mostly concerned with adult learners. This project focuses on addressing the need to improve the teaching of English as a second language to primary school children with hearing impairments. This paper presents the development of an educational software tool referred to as the Total Communication with Animation Dictionary (TCAD), which supports learners in the acquisition and retention of new English lexical knowledge and is based on the theoretical approaches of Total Communication and situated learning. A series of experiments was undertaken to evaluate the effectiveness of the TCAD in improving vocabulary acquisition and retention. Early results are promising with increased learner engagement and performance compared with traditional approaches.
_eprint: https://nasenjournals.onlinelibrary.wiley.com/doi/pdf/10.1111/j.1471-3802.2012.01239.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2012.01239.x 2339240:26Y8P2ER 2405685:SY4KMK35
Keywords: Hearing-impaired students; language acquisition; total communication with 3D animation

An animated dictionary for hearing-impaired students in Thailand - Wicha, Santichai; Sharp, Bernadette; Sureephong, Pradorn; Chakpitak, Nopasit; Atkins, Anthony (Journal of Research in Special Educational Needs, 2012)
As English increasingly becomes the international language, many ministerial and educational organisations have identified the need to improve the competence of Thai students in speaking English. While there is significant research devoted to developing software tools to support the teaching of English as a second language, they are mostly concerned with adult learners. This project focuses on addressing the need to improve the teaching of English as a second language to primary school children with hearing impairments. This paper presents the development of an educational software tool referred to as the Total Communication with Animation Dictionary (TCAD), which supports learners in the acquisition and retention of new English lexical knowledge and is based on the theoretical approaches of Total Communication and situated learning. A series of experiments was undertaken to evaluate the effectiveness of the TCAD in improving vocabulary acquisition and retention. Early results are promising with increased learner engagement and performance compared with traditional approaches.
4 citations (Crossref) [2024-02-28] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1471-3802.2012.01239.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2012.01239.x 2339240:3MKR4PR5 2405685:8227VXM4
Keywords: Hearing-impaired students; language acquisition; total communication with 3D animation; ⛔ No INSPIRE recid found

Revised Special Needs and Inclusive Education Policy - Ministry of Education (Republic of Rwanda, 2018)
EdTechHub.ItemAlsoKnownAs: 2405685:FIC7SLRH

Special Education and Deaf Children in Pakistan - Akram, Bushra; Bashir, Rukhsana (Journal of Elementary Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:9TKMBGYE 2405685:NQQMGAXE
Keywords: ⛔ No DOI found

Critical issues in advancing the special education technology evidence base - Edyburn, Dave L. (Exceptional Children, 2013)
Publisher: SAGE Publications Sage CA: Los Angeles, CA KerkoCite.ItemAlsoKnownAs: 10.1177/001440291308000107 2339240:CEK85TUR 2405685:CZ25UJQH

Report of the Special Rapporteur on extreme poverty and human rights - Alston, Philip (United Nations General Assembly, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:7DQX9NKE 2405685:M7L4IXDW

Mobile learning technology based on iOS devices to support students with special education needs - Fernández-López, Álvaro; Rodríguez-Fórtiz, María José; Rodríguez-Almendros, María Luisa; Martínez-Segura, María José (Computers & Education, 2013)
00026 shortDOI: 10/f4hnzg KerkoCite.ItemAlsoKnownAs: 10/f4hnzg 2129771:BFWDTZ88 2405685:VQRYXHV3

Why do we care about evidence synthesis? An introduction to the special issue on systematic reviews - White, Howard; Waddington, Hugh (Journal of Development Effectiveness, 2012)
Systematic reviews are currently in high demand in international development. At least 100 new reviews are ongoing or already completed on a range of topics across the board in international development, many of which were commissioned by policy-making agencies. These new reviews need to be based on answerable questions, using methods of analysis and reporting which are appropriate for social and economic development programmes and relevant to users. This introductory paper lays out why we believe systematic reviews should be an important component of evidence-informed development policy and practice. It concludes by introducing the papers collected in this issue, which aim to demonstrate how reviews can be made to live up to the promises generated around them.
shortDOI: 10/gf3t4g KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2012.711343 10/gf3t4g 2339240:9ZS4VDFU 2405685:REZFBZQW
Keywords: -FullBiblioUHMLgen; -GeneralCitations; 3ie; CLL:en; Reviewed; impact evaluation; publicImportV1; systematic reviews

The contribution of ICTs to the delivery of special educational needs in Ghana: practices and potent - Nkansah, Godfred Bonnah; Unwin, Tim (Information Technology for Development, 2010)
KerkoCite.ItemAlsoKnownAs: 10.1080/02681102.2010.497273 2339240:6W2XSNXE 2405685:GP3VLXGC

The Issues and Challenges of Using Multimedia at a District Level, Specialized Girls’ College in Bangladesh - Sarowardy, Muhammad Hasan; Halder, Deb Proshad (Creative Education, 2019)
The use of multimedia in imparting education has inevitably been trendy owing to its multifold benefits which have been established and reinvestigated as inseparable teaching aid and tool in teaching-learning process. But This technological assisting component cannot be accorded in many of the institutions of Bangladesh due to several internal as well as external factors. This paper aims to highlight the emerging factors that beset in the institution of Bangladesh. This institutional study on the issues and challenges of using of multimedia in a district (urban area) level girls’ college projects a thorough realization of the difficulties what this types of attributive colleges face in Bangladesh. The resource constraint, the lack of motivation of the teachers, the lack of expert human resource, the insufficient digital tools and lack of multimedia-enabled class environment are found to be barriers and some guiding directives are also imposed in this paper that emerges through the interviews of the teachers and the Vice principal. Thus, the paper, in a miniature effort, tries to lay out the challenges the college of Bangladesh faces and highlight some remedial ways to cope up the challenges.
KerkoCite.ItemAlsoKnownAs: 10/gj37jg 2339240:M5B3GAH9 2405685:LDBLDTX5

Special Needs Education (SNE) in Kenyan public primary schools: exploring government policy and teachers’ understandings - Mwangi, Lucy (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:UI9VSGAF 2405685:Y7LJH3SM 4656463:T688XI8F 4820577:YUAA6DRP
Keywords: ⛔ No DOI found

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=126003617&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2405685:BC5IPJP7 2534378:8GYBJJ8Z 2534378:R2HCJDDM
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

Innovative Strategies for Accelerated Human Resources Development in South Asia:: Information and Communication Technology for Education—Special Focus on Bangladesh, Nepal, and Sri Lanka - Asian Development Bank (Asian Development Bank, 2017)
Edition: 0 ISBN: 9789292610333 9789292610326 shortDOI: 10/ghgnfh KerkoCite.ItemAlsoKnownAs: 10.22617/TCS179080 10/ghgnfh 2339240:DC9GXZHD 2339240:H8XPPDHF 2405685:9CV4C8ZT 2405685:CIIMK9AK
Keywords: Systems Framework

Innovative strategies for accelerated human resource development in South Asia: Information and communication technology for education - Special focus on Bangladesh, Nepal, and Sri Lanka - ADB (Asian Development Bank, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:XPQH26KA 2405685:ZT5HV4GA

The use of computer-assisted instruction to improve the reading comprehension of students with learning disabilities: an evaluation of the evidence base according to the What Works Clearinghouse standards - Kim, Min Kyung; McKenna, John William; Park, Yujeong (Remedial and Special Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1177/0741932517693396 2339240:M673GYW8 2405685:PC4NHG5G

Using Information Communication Technologies (ICT) to Implement Universal Design for Learning (UDL) - Banes, David; Hayes, Anne; Kurz, Christopher; Kulshalnagar, Raja (University Research Co., LLC, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QM93JBAC 2405685:QDLCLTE4

Support for children and young people with vision impairment in educational settings (Welsh Government, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BVB4T4PT 2405685:PE87BSH7

What works? The case of inclusive education | Unesco IIEP Learning Portal - Singal, Nidhi (2018)
The Sustainable Development Goals with their commitment to ensuring all young people will have access to good quality primary and lower secondary education by 2030 have spearheaded an increased focus on children with disabilities. The SDGs explicit mention of persons with disabilities, across education and other goals have resulted in intense discussions on how to make these commitments a reality.
Library Catalog: learningportal.iiep.unesco.org KerkoCite.ItemAlsoKnownAs: 2339240:FHDY4ZTC 2405685:IJ7WBNAN IJ7WBNAN

Global perspectives on assistive technology: Proceedings of the GReAT Consultation 2019, Volume B - Day 2 (World Health Organization, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4KTX7RSQ 2405685:3DN8XRDU

Effective Use of Assistive Technologies for Inclusive Education in Developing Countries: Issues and challenges from two case studies - Grönlund, Åke; Lim, Nena; Larsson, Hannu (International Journal of Education and Development using ICT, 2010)
Developing countries face many obstacles in the process of implementing inclusive education (IE). Effective use of assistive technologies (AT) can help governments in developing countries achieve inclusive education by helping children with disabilities in schools. Despite the importance and positive impact of AT, prior research on the use of AT in inclusive education especially in developing countries is limited. To fill the research gap in this area, this paper investigates the research question of, How can AT be effectively used for IE in developing countries? To address this question,...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:MQSJ66AT 2405685:AYQJEEVW
Keywords: ⛔ No DOI found

GEM Report summary on disabilities in education (UNESCO, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:EZR4PD6B 2405685:X2YJQT9S

75 Digital Tools and Apps Teachers Can Use to Support Formative Assessment in the Classroom (Teach. Learn. Grow., 2019)
We’ve compiled an extensive list of 75 digital tools, apps, and platforms that can help teachers use formative assessment to elicit evidence of student learning. #education #teachers
Library Catalog: www.nwea.org Section: Formative Assessment KerkoCite.ItemAlsoKnownAs: 2339240:H4U5K8J7 2405685:WU8SHHQ8 WU8SHHQ8

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.07.002 2339240:MXTDK768 2405685:K9AQNHDY
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

Education and Disability in the Global South: new perspectives from Africa and Asia. London: Bloomsbury Publishing. - Singal, Nidhi; Lynch, P; Johansson, S. T (British Journal of Special Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1111/1467-8578.12292 2339240:EVTHNM88 2405685:3M6AJUNM

Universal Design for Learning to Help All Children Read: Promoting Literacy for Learners with Disabilities - Hayes, Anne; Turnbull, Ann; Moran, Norma (USAID, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:BQZXP46T 2405685:QAQ8FR9B

Towards a Disability Inclusive Education - Sæbønes, Ann-Marit; Bieler, Rosangela Berman; Baboo, Nafisa; Banham, Louise; Singal, Nidhi; Howgego, Catherine; McClain-Nhlapo, Charlotte Vuyiswa; Riis-Hansen, Trine Cecilie; Dansie, Grant Angus (Oslo Summit on Education for Development, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:JPKX5XBG 2339240:SSMZBC9V 2405685:3AIMPPZI 2405685:LDMG6PB8
Keywords: ___working_potential_duplicate

Inclusive Quality Education for Children with Disabilities - Singal, Nidhi; Ware, Hannah; Bhutani, Sweta Khanna (World Innovation Summit for Education & University of Cambridge, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:4ZA5WMI7 2339240:VS2APB8E 2339240:WALVDQHQ 2405685:B7XYHF4V 2405685:G784RVFY 2405685:UHVMVWIX

Education of children with disabilities in India and Pakistan: Critical analysis of developments in the last 15 years - Singal, Nidhi (PROSPECTS, 2016)
This article presents an analysis of key developments in educational policies and strategies, since 2000, in relation to the education of children with disabilities in India and Pakistan. It responds to a set of specific questions focused on factors that have shaped the increased emphasis on education of children with disabilities, how national policies and programmes respond to their needs, and their current educational status. The article draws on analysis of official policies, various programme documents, and empirical research evidence. It concludes by reflecting on the two main foci for future work in relation to the education of children with disabilities.
shortDOI: 10/gftstb KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-016-9383-4 10/gftstb 2339240:UC62U9Y7 2405685:V4R3ZU7R

Educational outcomes and research from 1:1 computing settings - Bebell, D.; O'Dwyer, L. M. (Journal of Technology, Learning, and Assessment, 2010)
Despite the growing interest in 1:1 computing initiatives, relatively little empirical research has focused on the outcomes of these investments. The current special edition of the Journal of Technology and Assessment presents four empirical studies of K-12 1:1 computing programs and one review of key themes in the conversation about 1:1 computing among advocates and critics. In this introduction to our 1:1 special edition, we synthesize across the studies and discuss the emergent themes. Looking specifically across these studies, we summarize evidence that participation in the 1:1 programs was associated with increased student and teacher technology use, increased student engagement and interest level, and modest increases in student achievement.
KerkoCite.ItemAlsoKnownAs: 2129771:TV2JLSG4 2405685:3HZ7QNKB
Keywords: ⛔ No DOI found

#CostingEquity: The case for disability-responsive education financing - Myers, Juliette; Pinnock, Helen; Baboo, Nafisa; Lewis, Ingrid (International Disability and Development Consortium, 2018)
The #CostingEquity research project investigated the benefits of financing disability-inclusive education, the current state of education financing with regard to inclusion, and what needs to change in order for education financing to effectively support the realisation of SDG 4. The #CostingEquity research report addresses three broad questions: • How do international donors and domestic governments currently fund disability-inclusive education? • What are the gaps and challenges in financing disability-inclusive education? • What needs to change to increase quality, equitable financing for learners with disabilities? The report aims to contribute to a better understanding of the issues related to equitable financing for education for learners with disabilities. It considers additional marginalising factors such as gender, socio-economic status, social circumstances and urban/rural location. It offers key arguments for civil society activists, donors and government advisors to make the case for building and strengthening inclusive education systems. Detailed case studies provide useful examples of financing gaps, challenges and promising practice from developing country contexts, major education donors, and new and emerging philanthropic donor foundations. The focus of case studies and examples is on low and lower-middle income countries and were chosen to reflect a broad range of regions and countries.The report concludes with a series of recommendations for domestic and external financing approaches.
KerkoCite.ItemAlsoKnownAs: 2339240:3XWFXVAP 2339240:DU3DQXWC 2405685:9WX2Z28W 2405685:EQP34VAJ

Inclusive early childhood education in Nigeria: the journey so far - Salami, Ishola Akindele (The Journal of International Association of Special Education, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:I8MLFP73 2405685:FVLMEIML
Keywords: ⛔ No DOI found

Higher education reforms: Latin America in comparative perspective - Bernasconi, Andrés; Celis, Sergio (Education Policy Analysis Archives, 2017)
This article introduces a special issue of EPAA/AAPE devoted to recent higher education reforms in Latin America. The last two decades have seen much policy development in higher education in the region, examined and discussed by scholars in each country, but dialog with the international literature on higher education reform, or an explicit comparative focus, have been mostly absent from these works. By way of presentation of the papers included in this issue, we first provide an overview of major policy changes in higher education in the Latin American region since the 1990s. We then turn to the six works in this special issue to describe the theories and methods supporting them. Next, we illustrate how general analytic categories can be derived from single or multi country case studies to illuminate themes capable of cutting across the particulars of national contexts, with their unique traditions, policy paths, and politics. Our three common threads are, first, the types of drivers for reform, that is, how policy change originates, either bottom-up from the institutions, or top-down from the government, and various possibilities in between. Second, understanding challenges to institutional autonomy in a continuum of intensity of state intended intervention in higher education. Third, explaining different levels of strain between public and private sectors in higher education based on conditions of competition for economic resources. While the papers in this special issue do not cover all countries, nor all issues on which policy has been crafted in the last two decades across the region, the collection of articles herein account for topics of enduring importance: faculty work in Ecuador, financial aid in Colombia, public policy decentralization in Argentina, quality assurance models in Colombia and Uruguay, the emerge of new institutions and universities in Argentina and Uruguay, and social justice, access, and inclusion in higher education, in Argentina, Bolivia, Brazil, Chile, Colombia, and Ecuador. The articles presented in this special issue provide much insight onto higher education policy in Latin America and, additionally, offer ample opportunity to develop social science knowledge on the basis of strong comparative work.
KerkoCite.ItemAlsoKnownAs: 10.14507/epaa.25.3240 2339240:4M24F399 2405685:RNRQL9Z2
Keywords: Change in universities

Mode of tele-communication and software used by children with hearing impairment - Zahra, Arjamand; Khan, Sikander Ghayas; Butt, Ayesha Kamal; Noreen, Hafsa; Saeed, Muhammad Imtiaz; Iftikhar, Nayab (Biomedical Research, 2018)
Objective: The study is being conducted to find out mode of tele-communication and software used by children with hearing impairment. Methodology: This cross-sectional study was done at special education centers and schools in Lahore and Sheikhupura. Data was collected from children with hearing impairment by using a questionnaire of 11 items about the modes of tele-communication and software used by children with hearing impairment. Sample size was 362 which was calculated by using online sample size calculator. The population includes male and female children with mild, moderate, severe and profound hearing impairment studying in special education schools of Lahore and Sheikhupura. All these children use hearing aid and have congenital bilateral hearing loss. Results: This study shows that almost 80% population of children with hearing impairment know about computer and mobile. They also have awareness about the use of computer, Facebook, e-mail etc. In addition, 40 to 50% children with hearing impairment use Skype, Facebook and e-mail as a communication tool. Conclusion: The conclusion from this study is that most of the children use computer and mobile on daily basis in schools and homes for communication. Mild to moderate hearing loss children benefit from these devices between the ages of 10 to 20 y.
Publisher: Biomedical Research KerkoCite.ItemAlsoKnownAs: 10.4066/biomedicalresearch.29-17-3494 2339240:7FCYX428 2339240:XZGUQ9KC 2405685:QFJGZFWK 2405685:U7CFTZ3Q

Problems of drop-out students in Indian slum - Siddiqui, Tarannum (International Education and Research Journal, 2017)
The purpose of this paper is to find out the problems of drop-out students at elementary level, specially living in slum areas of India. Educational facility at elementary level and its relationship with infrastructural facilities is the main focus of this paper. Paper highlights the role of government to improve elementary education in slum areas of the country with special focus on drop-out students. Paper is mainly based on primary and secondary data/ information. Study has taken a total sample of 50 households (25 from each district) by using random sampling technique in the urban areas namely- Madiyaon slum of Lucknow in Uttar Pradesh and Dharavi slum of Mumbai in Maharashtra. Intensive interviews have been conducted to procure purpose full information. The numbers of upper primary schools were found half of the primary schools in slum areas. Acording to RTE Act no students could be stop or retained in any class of primary section. To stop drop out situation at elementary level of education, paper recommends opening more government upper primary schools in the slum areas. Due to limited sample size, the research results may lack generalisation. Therefore, researchers and research institutions are encouraged to test the proposed propositions further. Dropping out from elementary education in slum areas are an unexplored area of research which has been covered in this paper.
Number: 5 KerkoCite.ItemAlsoKnownAs: 2339240:HJCCKF7J 2405685:W2QT6EH2
Keywords: Elementary education in slum areas.; Indian slums; Problems of drop-out students; ⛔ No DOI found

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Effects of gesture-based match-to-sample instruction via virtual reality technology for Chinese students with autism spectrum disorders - Hu, Xiaoyi; Han, Zhuo Rachel (International Journal of Developmental Disabilities, 2019)
Effective strategies to address academic performance are critical to students with disabilities in inclusive settings. The purpose of this study was to investigate the effectiveness of using gesture-based instruction via Leap Motion-aided virtual reality (VR) technology to teach matching skills to school-aged students with autism spectrum disorder (ASD) in China. Three participants with ASD from general education schools participated in this study. A multiple probe design across participants was used. The results indicated that all participants acquired the target match-to-sample skills and maintained the acquired skills at a high level for up to 12 weeks. Results of this study provide important implications to special education and general education teachers working with students with ASD.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20473869.2019.1602350 KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2019.1602350 2339240:XFCC6MFH 2405685:2Q77DSNT
Keywords: China; autism spectrum disorders; computer-assisted instruction; gesture-based; match-to-sample; virtual reality technology

Using Universal Design for Learning to design standards-based lessons - Rao, Kavita; Meo, Grace (Sage Open, 2016)
The Universal Design for Learning (UDL) framework can be used to proactively design lessons that address learner variability. Using UDL guidelines, teachers can integrate flexible options and supports that ensure that standards-based lessons are accessible to a range of learners in their classrooms. This article presents a process that teachers can use as they develop standards-based lesson plans. By “unwrapping” academic standards and applying UDL during the lesson planning process, teachers can identify clear goals aligned with an academic standard and develop flexible methods, assessments, and materials that address the needs and preferences of varied learners. General educators and special educators can use this process to develop inclusive lesson plans that address all learners, with and without disabilities.
KerkoCite.ItemAlsoKnownAs: 10.1177/2158244016680688 2339240:W4M6LDLT 2405685:S42A7PKF

iPad: efficacy of electronic devices to help children with autism spectrum disorder to communicate in the classroom - Sankardas, Sulata Ajit; Rajanahally, Jayashree (Support for Learning, 2017)
Children with Autism Spectrum Disorder (ASD) are known to have difficulty in social communication, with research indicating that children with ASD fail to develop functional speech (Lord and Rutter, 1994). Over the years a number of Augmented and Alternate Communication (AAC) devices have been used with children with ASD to overcome this barrier and to facilitate communication. This article examines an Indian AAC tool called AVAZ (meaning sound), which is the first of its kind in India. The project reported also looks at the effectiveness of using AVAZ and the use of iPads by children with ASD in the classroom. Additionally, the article examines the suitability of using iPads for all learners in the spectrum. Twenty children between the ages of 4 and 10 years were selected to trial the use of AVAZ. They received three sessions weekly of 45 minutes over a period of 10 weeks. The feedback of the special educators who trained the children was analysed. The findings of this small scale study indicates that the children preferred using the AVAZ app and the iPad to pen and paper. Huguenin (2004) too indicated similar reports in using Information and Communication Technology (ICT) in enhancing children's motivation to learn and communicate. The trainers felt it could be used as an educational tool, and many more educational concepts could be added. Research also suggests that ICT can be used as a tool to tutor for educational purpose (Means, 1994). The AVAZ app could be recommended to children with ASD who are included in mainstream schools. This study was conducted at Sankalp, a special school in Tamil Nadu, Chennai.
_eprint: https://nasenjournals.onlinelibrary.wiley.com/doi/pdf/10.1111/1467-9604.12160 KerkoCite.ItemAlsoKnownAs: 10.1111/1467-9604.12160 2339240:B3KGPHPK 2405685:R92QINFG
Keywords: alternate and augmented communication; autism spectrum disorder; information and communication technology; social communication

ICTs in Learning in Pakistan - Hassan, Taimoor; Sajid, Ar (International Journal of Evaluation and Research in Education (IJERE), 2012)
The paper investigates the barriers to the integration of Information and Communication Technologies (ICTs) at secondary level learning in Pakistan, with special emphasis on Punjab province. Exploring major barriers to the integration of ICTs at the school level, teacher level and student level and possible enablers to these barriers is the major focus of study. Sequential mixed method design is used. Interviews were analysed qualitatively whereas survey questionnaire were analysed quantitatively. It is observed from the findings that most of the participants have positive perceptions about integration of ICTs into their teaching and learning. Administrators and ICT coordinators revealed many barriers and possible enablers to the integration of ICTs. Many of these barriers are verified by the teachers and students. Later on however there were some barriers which were not endorsed by the teachers and students.
KerkoCite.ItemAlsoKnownAs: 10.11591/ijere.v1i2.1244 2339240:N34T78WC 2405685:5INDIDCV

Computer-Adaptive Testing for Students with Disabilities: A Review of the Literature - Stone, Elizabeth; Davey, Tim (ETS Research Report Series, 2011)
There has been an increased interest in developing computer-adaptive testing (CAT) and multistage assessments for K-12 accountability assessments. The move to adaptive testing has been met with some resistance by those in the field of special education who express concern about routing of students with divergent profiles (e.g., some students with math-based learning disabilities may have difficulty with basic computation but not high level problem solving) and poor performance on early test questions. This paper consists of a literature review focusing on adaptive testing issues for students with disabilities in the K-12 sector. While it is clear that there are issues that will present obstacles to administering accountability tests adaptively to students with disabilities, this synthesis of research and policy developments with respect to this topic will be useful both for development of research agendas and to inform states that are currently using or are considering moving to CAT.
KerkoCite.ItemAlsoKnownAs: 10.1002/j.2333-8504.2011.tb02268.x 2339240:A69MIC83 2405685:UQW6AGZS

Using Educational Games for Sign Language Learning - A SignWriting Learning Game: Case Study - Bouzid, Yosra; Khenissi, Mohamed Ali; Essalmi, Fathi; Jemni, Mohamed (Journal of Educational Technology & Society, 2016)
ABSTRACT Apart from being used as a means of entertainment, computer games have been adopted for a long time as a valuable tool for learning. Computer games can offer many learning benefits to students since they can consume their attention and increase their motivation and engagement which can then lead to stimulate learning. However, most of the research to date on educational computer games, in particular learning versions of existing computer games, focused only on learner with typical development. Rather less is known about designing educational games for learners with special needs. The current research presents the results of a pilot study. The principal aim of this pilot study is to examine the interest of learners with hearing impairments in using an educational game for learning the sign language notation system SignWriting. The results found indicated that, overall, the application is useful, enjoyable and easy to use: the game can stimulate the students' interest in learning such notations.
KerkoCite.ItemAlsoKnownAs: 2339240:DXXIUF8I 2405685:L83ZWRA2
Keywords: ⛔ No DOI found

The Effectiveness and Usability of the Educational Software on Concept Education for Young Children with Impaired Hearing - Goker, Hanife; Ozaydin, Latife; Tekedere, Hakan (EURASIA Journal of Mathematics, Science & Technology Education, 2016)
Early intervention and early education have a special place in educating the children with Impaired Hearing (IH). The advancements in information and communication technologies have led to adopting the view that such technologies could be applied in the educational process of the children with IH. Besides, the positive results acquired in the studies conducted in the light of this review have brought up the fact that proper technology-based educational environments should be provided and popularized for the young children with IH. In this study, educational software has been developed for the purpose of teaching emotions and opposite concepts to young children with IH. With this software, videos with topic descriptions, games reinforcing funny and topic-based learning, questions and audio-visual feedbacks have been used. The effectiveness of this software in concept education along with its usability by children has been examined; and in addition, the subjective viewpoints of the teachers of students with IH on this software have been consulted as well.
KerkoCite.ItemAlsoKnownAs: 10.12973/eurasia.2016.1207a 2339240:LS7NEM49 2405685:CW2LUTWC

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RPKBXC8H 2405685:XNWLCKWJ

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR10.100 2339240:B8RGF7UM 2405685:ZSVGWH7J

The Simple, the Complicated, and the Complex: Educational Reform Through the Lens of Complexity Theory - Snyder, Sean (2013)
This paper explores the nature of complexity theory and its applications for educational reform. It briefly explains the history of complexity theory and identifies the key concepts of complex adaptive systems, and then moves on to define the differences between simple, complicated, and complex approaches to educational reform. Special attention is given to work currently underway in the fields of healthcare, emergency management and ecology that draws on complexity theory to build more resilient and robust response systems capable of adapting to changing needs and of identifying key pressure points in the system. Finally, this paper presents several examples of educational reform programmes undertaken worldwide that have implemented complexity theory principles to achieve positive results. It also recommends involving multiple stakeholders across the different levels of governance structure, increasing lateral knowledge-sharing between schools and districts, and transforming policy interventions to bring greater flexibility to the reform process. This move toward feedback-driven adaptive reform allows for better targeting of programmes to specific contexts and may prove a key way forward for educational policymakers.
Series: OECD Education Working Papers Volume: 96 zotzenLib.CopiedFrom: 2339240:4NV7VJ5R KerkoCite.ItemAlsoKnownAs: 10.1787/5k3txnpt1lnr-en 2339240:4NV7VJ5R 2405685:86KPU7TF

Training with ICT for ICT from the trainee’s perspective. a local ICT teacher training experience - Kalogiannakis, Michail (Education and Information Technologies, 2010)
The introduction of ICT (Information and Communication Technologies) presents new challenges for teachers and often meets with their belief that ICT, as well as other changes present a factor, which can cause several changes in school. Although there have been many education reforms regarding teachers’ training policy in recent years and the number of training programs has been increased, they have not been able to satisfy teachers’ needs to a substantial degree. In this research the results from an exploratory study conducted within the framework of a national training programme in Greece on ICT known as "In-service teacher training in the use of ICT in Education" are presented. Based on a specially constructed questionnaire intended for the educators, this research elicits teachers’ attitudes towards this programme. Some of the main results point out the preparedness of these teachers to use ICT in the daily school practice. Furthermore, they expressed their wish for further in-training programmes concerning the pedagogical development of the ICT use in class practice. KeywordsIn-service training-Teachers-ICT-Greece
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-008-9079-3 2339240:T9FFA6HC 2405685:DXHT4AIY

Teaching linear algebra supported by GeoGebra visualization environment - Aytekin, Cahit; Kiymaz, Yasemin (Acta Didactica Napocensia, 2019)
Linear algebra differs from other mathematics courses because of the special difficulties that students have in understanding the concepts. Teaching without concretizing the concepts of Linear Algebra encouraged students to memorize definitions of concepts and rules has been articulated. Many researches show that technology-supported teaching is effective in concretizing abstract concepts. In this study, it was examined how pre-service mathematics teachers relate the definitions of concepts (linear combination, linear dependency/independency and spanning) and their visual equivalents in R[superscript 2] and R[superscript 3]. The study was conducted with four students who attended the Linear Algebra-2 course in the Elementary Mathematics Teaching, Faculty of Education of a state university in Turkey. The study was conducted by the teaching experiment method. Interviews were conducted using activities prepared in the GeoGebra program. It was observed that the participants used these concepts in very flexible way and they established a relationship between visualization and definitions in a very short time compared to the time spent during an educational period.
Publisher: Babes-Bolyai University, Kogainiceanu 1, Cluj-Napoca, 400084 Romania Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2396823562?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.24193/adn.12.2.7 2339240:BJHHRSRN 2405685:SNEABJDN 2534378:G2ILAXW6 2534378:J8FUJBYM
Keywords: Algebra; Computer Software; Definitions; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Foreign Countries; Higher Education; Mathematics Instruction; Mathematics Teachers; Postsecondary Education; Preservice Teachers; Teaching Methods; Technology Uses in Education; Turkey; Visualization; __:import:01; __:match:final; __:matched; __:study_id:2099267; __finaldtb

Public vs Private Quality Education at Primary Level in Pakistan - Farooq, Muhammad Sabil; Feroze, Nazia; Kai, Yuan Tong (International Online Journal of Primary Education, 2017)
Pakistan is an ethnically and religiously diverse country of over 190 million people. There are 22.6 million boys and girls out of school that's nearly half (44%) of all children in the country. This study was designed to assess comparative quality measures of primary level education at both public and private institutions of Pakistan. This study based on secondary data specially focused on ASER Pakistan Survey Report 2015 that was conducted in 146 rural districts of Pakistan, covering 83,755 households in 4,217 villages throughout the country. Detailed information was collected on 258,021 children (59% males, 41% females) aged 3-16 years. Out of these 219,609 children aged 5-16 years were tested for language and arithmetic competencies. It was found that Public schools lacking with trained teaching staff, well equipped classrooms and good policy and administration. While the other hand private schools deficient of well-educated staff, good infrastructure and self-motivation. It was recommended that the Government needs to realize this situation and to equalize the standards of public and private sector to achieve vigorous quality education at this level.
Publisher: International Online Journal of Primary Education KerkoCite.ItemAlsoKnownAs: 2339240:JRSDGKRM 2405685:BSNTWHMM
Keywords: Academic Achievement; Arithmetic; Educational Administration; Educational Policy; Educational Quality; Educational Resources; Elementary Education; Elementary School Students; Foreign Countries; Literacy; Mathematics Skills; Private Education; Public Education; Secondary School Students; Socioeconomic Influences; Teacher Competencies; ⛔ No DOI found

A computational literature review of the field of System Dynamics from 1974 to 2017 - Kunc, Martin; Mortenson, Michael J.; Vidgen, Richard (Journal of Simulation, 2018)
System Dynamics celebrated its 60th anniversary in 2017. While there have been numerous special issues in diverse journals that bring together work by System Dynamics scholars who share similar research interests, there have been no systematic reviews of scholarly activity across the broad field. This paper presents a computational literature review of the field from 1974 to 2017. A CLR automates the analysis of research articles with analysis of content (topic modelling of abstracts) to identify emergent themes in the literature. We performed a broad review of the field by initially searching using the term “System Dynamics” with more than 8000 articles. However, the results obtained were not satisfactory so we decided to restrict our sample to less than 800 articles from recognised journals and proceedings. After evaluation of the results obtained from topic modelling, we decided to use 51 topics covering most of the articles in our sample. A list of 51 topics provides enough granularity to identify relevant patterns of activity within the community of System Dynamics scholars. For each of these 51 topics, we present a commentary on the key insights obtained.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/17477778.2018.1468950 KerkoCite.ItemAlsoKnownAs: 10.1080/17477778.2018.1468950 2405685:KNZA7VQE 2486141:2X7SQ6MJ 2486141:Y3KUR5CN
Keywords: System Dynamics; computational literature review; healthcare; methodology; supply chain

The Impact of ICT as Another Route to Overcome Learning Barriers for Students with SEN: A Case Study in an Egyptian Context - Al-Gawhary, Wedad; Kambouri, Maria (International Association for the Development of the Information Society, 2012)
The purpose of this case study was to measure the impact of using ICT in Individual Learning Programmes of students with learning disabilities. Twenty five students and thirteen teachers took part in the research which was based on classroom observations. The Kappa coefficient was employed as a measure to statistically quantify the students' acquisition and progress in learning computer and literacy skills through raters' observations. A high correlation between Keyboard, PowerPoint, and literacy skills (writing, reading, and maths) was revealed suggesting the significance and impact of keyboard training as an essential component towards achieving educational objectives. Moreover, thematic analysis of the teachers' interviews provided a further dimension for understanding factors influencing the ICT integration process. These results further confirmed the positive impact of computer skills training on the students' learning experience which also revealed a strong belief in the right of every child to all learning opportunities, particularly ICT regardless of his/her abilities.(Contains 2 tables.) [For the complete proceedings, "Proceedings of the International Association for Development of the Information Society (IADIS) International Conference on Cognition and Exploratory Learning in Digital Age (CELDA) (Madrid, Spain, October 19-21, 2012)," see ED542606.]
Publication Title: International Association for Development of the Information Society KerkoCite.ItemAlsoKnownAs: 2339240:95DQ5J33 2405685:M5TD7M7N
Keywords: Autism; Barriers; Case Studies; Cerebral Palsy; Communications; Computer Literacy; Computer Mediated Communication; Computer Software; Down Syndrome; Foreign Countries; Heterogeneous Grouping; Information Technology; Interrater Reliability; Mixed Methods Research; Semi Structured Interviews; Semitic Languages; Special Needs Students

When does ICT support education in South Africa? The importance of teachers' capabilities and the relevance of language - Gudmundsdottir, G. B. (Information Technology for Development, 2010)
The aim of this paper is to highlight some of the challenges of information and communication technology (ICT) integration in a South African classroom setting. The main focus is on the concept of a digital divide, and how cultural complexity with special emphasis on language can affect the divide in schools that already have material access to ICT. The study is based on fieldwork in seventh-grade classes in four primary schools in Cape Town, South Africa. The learners answered a questionnaire regarding their ICT use and skills, and interviews were conducted with learners, teachers, and principals. In conclusion, it is argued that the challenges of language in South African schools can exacerbate or maintain the digital divide among learners who are already disadvantaged due to a range of social inequalities. For learners to fully master the use of ICT in today's global knowledge society, it needs to be put in a local context, which includes use in a familiar language. Moreover, it is suggested that greater opportunities for teacher training are needed in order to enhance culturally sensitive and appropriate ICT integration based on local needs and capacity.
Publisher: Routledge _eprint: https://doi.org/10.1080/02681102.2010.498409 KerkoCite.ItemAlsoKnownAs: 10.1080/02681102.2010.498409 2405685:U9M2N3BV 4042040:YQYVKVPN
Keywords: ICT integration; digital divide; disadvantaged learners; language of teaching and learning; teacher training

Mobile learning and student cognition: A systematic review of PK-12 research using Bloom’s Taxonomy - Crompton, Helen; Burke, Diane; Lin, Yi-Ching (British Journal of Educational Technology, 2019)
The rise of mobile learning in schools during the past decade has led to promises about the power of mobile learning to extend and enhance student cognitive engagement. The purpose of this study was to examine trends to determine the cognitive level students are involved in within mobile learning activities. This systematic review involved an aggregated and configurative synthesis of PK-12 mobile learning studies from 2010 to 16 and used Bloom’s Taxonomy as a theoretical framework for categorizing the cognitive level of student activities. Major new findings include that students are involved in activities at all six levels of Bloom’s Taxonomy. This study shows that over 60% of researchers are developing activities that require high levels of cognitive processing, a large increase from past studies. Nonetheless, 40% are integrating mobile devices in ways that keep students working with minimal cognitive processing. In both elementary and secondary studies, there was a 40/60% split in the use of lower versus high level thinking opportunities. New findings show that mobile devices were integrated into science, mathematics, social studies, literacy, art and special education. Studies in science settings were the majority of the studies (40%), followed by literacy (24%).
shortDOI: 10/gf5f7g KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12674 10/gf5f7g 2339240:ITSJB3B5 2339240:KIEJIK2D 2405685:J23Q8BH4
Keywords: Reviewed

Tiblo: a tangible learning aid for children with dyslexia - Pandey, Sumit; Srivastava, Swati (Procedings of the Second Conference on Creativity and Innovation in Design, 2011)
Dyslexia is a learning disability, which affects the ability to read and spell correctly. Special schools for children with dyslexia focus on individual growth, learning and psychological difficulties faced by the child. In this paper, we describe the design, development and testing of Tiblo (Tangible Interactive BLOcks), a tangible learning aid for children with dyslexia in the age group of 8 to 12 years. Tiblo has been specifically designed keeping in mind the psychological and emotional effects of dyslexia. We explain the process and results of an ethnographic study conducted at a school for children with dyslexia; the resulting concept development and prototyping. Further, we outline the testing process with the students at the school and the results of the same. The results showed that the children have a greater engagement in their classroom activities and there is an improvement in their retention abilities on using Tiblo. Also, they had a very strong sense of attachment and ownership towards the blocks and like to personalize it. This was in sharp contrast with other digital learning aids which offer a symptomatic and subject specific approach to aiding children with dyslexia and hence do not develop a personal one to one relationship with the child.
KerkoCite.ItemAlsoKnownAs: 10.1145/2079216.2079247 2339240:99N4A4R8 2405685:ACZ65MR7
Keywords: collaborative learning; design case study; dyslexia; emotional design; interaction design; learning aids; play and learn; tangible user interfaces

The design and testing of multimedia for teaching arithmetic to deaf learners - Techaraungrong, Piyaporn; Suksakulchai, Surachai; Kaewprapan, Wacheerapan; Murphy, Elizabeth (Education and Information Technologies, 2017)
The purpose of the study reported on in this paper was to design and test multimedia for deaf and hard of hearing (DHH) learners. The study focused on counting, addition and subtraction with grade one (age 7) DHH learners in Thailand. The multimedia created for the study was informed by design considerations for DHH learners of arithmetic and aimed to minimize cognitive load. Testing took place over a period of 16 weeks during which learners alternated between 2 and 3 week sessions of one hour per day with multimedia (numbers 1–10) versus 2–3 week sessions of one hour per day with the teacher (numbers 11–20). Results of the design included features such as non-essential use of text, reliance on non-symbolic objects, user control, and signals to relevant content. Results of testing showed that learning with multimedia resulted in higher scores than learning with the teacher (Z = 4.545, p = 0.000). Post-intervention interviews highlighted the role of motivation, ease of comprehension and independent learner control of the multimedia. The conclusion highlighted the need for multimedia design principles that reflect a more inclusionary focus on children with special needs such as those featured in this study.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9441-1 2339240:CZT5XWYH 2405685:DK3Y33G7

Working for my dreams - a Tanzanian OLPC experience - Duveskog, M.; Sedano, C. I.; Sutinen, E. (2010 IST-Africa, 2010)
Students at Tumaini University in Tanzania won a prestigious OLPC project where Ukombozi primary school in Tanzania was given 100 XO laptops for the children at the school. After teachers and students had undertaken basic training in using the laptops the workshop “Working for my Dreams” was organized at the school. The XO laptop, specially designed for young learners in developing countries showed a number of short comings including the poor functionality of the mouse, difficulties in installing additional applications and the limited storage space, which raised several questions around the technology and its usefulness. Much time was spent on figuring out solutions on how to use the XO laptops for basic things such as showing recorded videos in the browser which would have been minor tasks on any other commercially available platform. The outcome of the workshop was however a success and XO was eventually able to perform according to our needs for the workshop. We will evaluate the XO platform based on the context of Ukombozi primary school and on the tasks required of the XO laptop for the success of the workshop. The technical challenges encountered during the workshop and our solutions in overcoming the challenges will be discussed.
KerkoCite.ItemAlsoKnownAs: 2339240:JL9XPEWL 2405685:PG3IVJWK
Keywords: Conferences; Context; Educational institutions; Human immunodeficiency virus; Materials; OLPC; OLPC project; Portable computers; Tanzania; Tumaini University; Ukombozi primary school; XO; XO laptops; application installation; computer based training; context; developing countries; dreams; educational institutions; laptop computers; mouse; mouse controllers (computers); storage space; training; working for my dreams; workshop; ⛔ No DOI found

The design and testing of multimedia for teaching arithmetic to deaf learners - Techaraungrong, Piyaporn; Suksakulchai, Surachai; Kaewprapan, Wacheerapan; Murphy, Elizabeth (Education and Information Technologies, 2015)
The purpose of the study reported on in this paper was to design and test multimedia for deaf and hard of hearing (DHH) learners. The study focused on counting, addition and subtraction with grade one (age 7) DHH learners in Thailand. The multimedia created for the study was informed by design considerations for DHH learners of arithmetic and aimed to minimize cognitive load. Testing took place over a period of 16 weeks during which learners alternated between 2 and 3 week sessions of one hour per day with multimedia (numbers 1–10) versus 2–3 week sessions of one hour per day with the teacher (numbers 11–20). Results of the design included features such as non-essential use of text, reliance on non-symbolic objects, user control, and signals to relevant content. Results of testing showed that learning with multimedia resulted in higher scores than learning with the teacher (Z = 4.545, p = 0.000). Post-intervention interviews highlighted the role of motivation, ease of comprehension and independent learner control of the multimedia. The conclusion highlighted the need for multimedia design principles that reflect a more inclusionary focus on children with special needs such as those featured in this study.
8 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9441-1 2339240:EEJYTIKF 2405685:DDVUKNXB
Keywords: Arithmetic; Cognitive load; Deaf and hard of hearing; Design; Multimedia; Testing; ⛔ No INSPIRE recid found

Community Development through Open Learning and Distance Education - Mehmood, Tahir; Hussain Ch, Abid; Saeed, Amna (Bulletin of Education and Research, 2016)
The global need for community development is greater now in the early 21st century than ever before. According to UNESCO, half of the world's 195 countries will have to expand their stock of educationist significantly, some by tens of thousands, if the goal development targets are desired to achieve. Socioeconomic inequities, political instability, demographic changes and crises such as the HIV/AIDs epidemic have engendered huge shortfalls in teacher supply and low teacher quality in many developing countries. Education serves as back bone in development process. Open learning and distance education programs are serving as pivotal part of development process. It is now clear that "bricks and mortar" approaches to expanding teacher education may not be adequate if the current and projected shortfalls in teacher supply and low teacher quality are to be properly addressed. The study is designed to measure the perceptions of teaching learning community about community development with special reference to open and distance learning. It was descriptive study which targeted teachers, students, community members and experts. Data analysis was carried out by using statistical techniques served by SPSS. Findings reflected that audience perceives open and distance learning as change agent and as development tool. It is noticed that target audience has driven prominent performance by using facility of open and distance learning.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:VXX3G7KQ 2405685:GTVRNDQ9
Keywords: Access to Education; Change Agents; Community Development; Developing Nations; Distance Education; Economic Development; Educational Change; Educational Quality; Foreign Countries; Gender Differences; Nongovernmental Organizations; Open Educational Resources; Social Differences; Specialists; Student Attitudes; Teacher Attitudes; Teacher Shortage; ⛔ No DOI found

Gender differences in computer and information literacy: An in-depth analysis of data from ICILS - Gebhardt, Eveline; Thomson, Sue; Ainley, John; Hillman, Kylie (Springer Nature, 2019)
This open access book presents a systematic investigation into internationally comparable data gathered in ICILS 2013. It identifies differences in female and male students’ use of, perceptions about, and proficiency in using computer technologies. Teachers’ use of computers, and their perceptions regarding the benefits of computer use in education, are also analyzed by gender. When computer technology was first introduced in schools, there was a prevailing belief that information and communication technologies were ‘boys’ toys’; boys were assumed to have more positive attitudes toward using computer technologies. As computer technologies have become more established throughout societies, gender gaps in students’ computer and information literacy appear to be closing, although studies into gender differences remain sparse. The IEA’s International Computer and Information Literacy Study (ICILS) is designed to discover how well students are prepared for study, work, and life in the digital age. Despite popular beliefs, a critical finding of ICILS 2013 was that internationally girls tended to score more highly than boys, so why are girls still not entering technology-based careers to the same extent as boys? Readers will learn how male and female students differ in their computer literacy (both general and specialized) and use of computer technology, and how the perceptions held about those technologies vary by gender.
Accepted: 2020-03-18 13:36:15 Journal Abbreviation: An In-depth Analysis of Data from ICILS KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-26203-7 2339240:WGHTZ8T5 2405685:7BDLRHWK

Teaching children with disabilities: ICTs in Bangkok and Addis Ababa - Schiemer, Margarita; Proyer, Michelle (Multicultural Education & Technology Journal, 2013)
Purpose – This paper intends to explore the levels of availability and restrictions in relation to the use of ICTs (information and communication technologies) for educating children with disabilities in Thailand's and Ethiopia's capitals. Design/methodology/approach – In the course of an international research project, parents and teachers of children with different disabilities, the children themselves and further experts were interviewed about barriers and facilitators in the children's educational environment. For this paper only selected interviews focusing on sensory disabilities were analysed regarding the above mentioned areas of using ICTs. Findings – ICTs are available in the respective cities. The levels of restrictions related to the socio‐economic situation in the two cities vary accordingly but show the same overall limitations. The intensity and kind of use of ICTs is strongly related to resources, the educational actors' awareness and knowledge. Originality/value – Approaching the topic of ICTs in relation to disability might not be new, neither is the contextualisation with the Majority World. However, the combination of the three aspects against the background of current global developments (e.g. the growing gap between the poor and the rich) reveals the importance of taking a closer look at special needs education and ICTs in the Majority World. This opens the floor for discussion on how inclusion of the most marginalised groups in education affects development in general.
3 citations (Crossref) [2024-02-28] Publisher: Emerald Group Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/17504971311328026 2339240:8W9UMMQG 2339240:HT2CTPM2 2405685:5AVSEAD3 2405685:6SYB238I
Keywords: Children; Children with disabilities; Comparative research; Disabilities; Education; Ethiopia; ICTs; Majority World; Thailand; include (age level unclear); ⛔ No INSPIRE recid found

Games for enhancing basic reading and maths skills: A systematic review of educational game design in supporting learning by people with learning disabilities - Lämsä, Joni; Hämäläinen, Raija; Aro, Mikko; Koskimaa, Raine; Äyrämö, Sanna-Mari (British Journal of Educational Technology, 2018)
The development of games for people with learning disabilities is one way to enhance the quality of learning and respond to the need for inclusive special educational support. Recently, game researchers have highlighted the need for paying more attention to identifying the game design choices that can strengthen learning. This paper reviews recent studies in the field of games that aim at supporting people with difficulties in learning, particularly in basic reading and maths skills. We identify the major characteristics and learning outcomes of the reviewed studies, as well as key design principles that have been used in games for enhancing basic reading and maths skills. The results show that people with specific learning difficulties have positive improvements in the quality of learning. We also found specific gamification elements that have been used to promote the learning of basic reading and maths skills. However, we call for research, which would explicitly examine the effects of game design choices on learning. Currently, the studies that address learning disabilities do not specifically define which kind of games and game design the results refer to, while game design studies do not clarify how these games influence learning. Thus, there is a need to rethink previous empirical studies on game settings for people with learning difficulties via advancing the role of game design in empirical intervention studies.
shortDOI: 10/gd2h8p KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12639 10/gd2h8p 2339240:FUFE3LCB 2405685:RTFGP4FK
Keywords: Reviewed

Teaching children with disabilities: ICTs in Bangkok and Addis Ababa - Schiemer, Margarita; Proyer, Michelle; Ahamer, Gilbert (Multicultural Education & Technology Journal, 2013)
Purpose – This paper intends to explore the levels of availability and restrictions in relation to the use of ICTs (information and communication technologies) for educating children with disabilities in Thailand's and Ethiopia's capitals. Design/methodology/approach – In the course of an international research project, parents and teachers of children with different disabilities, the children themselves and further experts were interviewed about barriers and facilitators in the children's educational environment. For this paper only selected interviews focusing on sensory disabilities were analysed regarding the above mentioned areas of using ICTs. Findings – ICTs are available in the respective cities. The levels of restrictions related to the socio‐economic situation in the two cities vary accordingly but show the same overall limitations. The intensity and kind of use of ICTs is strongly related to resources, the educational actors' awareness and knowledge. Originality/value – Approaching the topic of ICTs in relation to disability might not be new, neither is the contextualisation with the Majority World. However, the combination of the three aspects against the background of current global developments (e.g. the growing gap between the poor and the rich) reveals the importance of taking a closer look at special needs education and ICTs in the Majority World. This opens the floor for discussion on how inclusion of the most marginalised groups in education affects development in general.
KerkoCite.ItemAlsoKnownAs: 10.1108/17504971311328026 2339240:V5YTXAA5 2405685:2KZYYG9Y
Keywords: Children; Children with disabilities; Comparative research; Disabilities; Education; Ethiopia; ICTs; Majority World; Thailand

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
Various curricular and textbook initiatives exist to aid in the national processes of coming to terms with past violence, often serving the political goals of the victors, sometimes supported by international transitional justice institutions. Sierra Leone and Liberia each experienced a devastating civil war during the 1990s and into the 2000s, and each is struggling to rebuild shattered education systems. In addition, each country has experienced a set of post-conflict transitional justice initiatives: Truth and Reconciliation Commissions in each, and a Special Court for Sierra Leone. Although their respective ministries of education have attempted to address peace education through UNICEF-sponsored curriculum revision processes, those efforts have not yet reached the majority of serving teachers, so a discussion of teachers’ actual practices is vital. This article uses interviews with teachers in rural and urban Sierra Leone and Liberia to discuss whether and how teachers talk about past war in their classrooms; whether they think it is important to discuss past conflicts, and if so, why; and what kind of curricular support would help them better teach about the wars. The article discusses how and why teachers embrace or subvert official efforts through their classroom practices, and compares the Sierra Leone and Liberia contexts and results. This research will help us to understand teachers’ own perspectives on addressing past conflict in their classrooms, and perhaps help policy-makers better implement their peace education initiatives.
Publisher: Routledge _eprint: https://doi.org/10.1080/03050068.2017.1338641 KerkoCite.ItemAlsoKnownAs: 10.1080/03050068.2017.1338641 2405685:9FVX5LB3
Keywords: Education; Liberia; Sierra Leone; teachers; teaching about conflict; transitional justice

A Study of the Application of Information Technology in Distance Education in Pakistan - Gujjar, Aijaz Ahmed; Ahmed, Saira Ijaz; Ramzan, Muhammad (Journal of Educational Technology, 2011)
Education plays a vital role to develop the nation culturally, economically and socially. That is why every nation focuses on this sector. For its improvement all endeavors are being made through formal education, Non-formal education and Distance Education. The trend of distance education has developed considerably in developed countries and developing countries. Information technology plays a pivotal role for the development of Distance Education. Keeping in view the importance of I.T. in education, this study was developed. The main aim of this study was to investigate the use of information technology in distance education in Pakistan. Population comprised of the I.T. users, person helping, operating or supervising the I.T. tools as planners, academicians, designers, programmers, producers, operators, regional directors and Deans of AIOU. Questionnaire on five point Likert scale was prepared. Collected data was tabulated and analyzed. The main conclusions of the study are: The use of information technology is still limited. Computer net work was not used for distance learners, Radio, T.V. programs and relevant audio material, videocassettes were prepared and CDs, software still not in use. University library was not computerized. Staff got training from time to time in I.T. Education in their specialization. But there is need to make I.T. system more sophisticated according to new trends and students' needs. There is also need to develop regional centers, which should serve as resource centers to the facilitation of distance learners.
Publisher: i-manager Publications KerkoCite.ItemAlsoKnownAs: 10.26634/jet.7.4.1389 2339240:GMBSS6P7 2405685:F2XC3TFE
Keywords: Access to Information; Data Analysis; Data Collection; Distance Education; Electronic Libraries; Foreign Countries; Information Technology; Likert Scales; Nonformal Education; Open Universities; Questionnaires; Radio; Scores; Statistical Analysis; Student Needs; Technology Uses in Education; Television; Trend Analysis; Use Studies

International review of the literature of evidence of best practice models and outcomes in the education of blind and visually impaired children - Douglas, Graeme; McLinden, Mike; Steve, McCall; Pavey, Susan; Ware, J; Farrell, A (National Council for Special Education (NCSE), 2010)
KerkoCite.ItemAlsoKnownAs: 2339240:45QZZCB8 2405685:MZA7MRZ8

"For us it was a learning experience": design, development and implementation of blended learning - Onguko, Brown; Jepchumba, Lucy; Gaceri, Petronilla (European Journal of Training and Development, 2013)
Purpose - The purpose of this paper is to share reflections of the three authors on the process of instructional design and implementation of blended learning for teachers' professional development (PD) in rural western Kenya. It proposes reforms in provision of teachers' professional development to enable professional development providers to access specialized skills in instructional design (ID) and blended learning. Design/methodology/approach - The paper resulted from a design-based research including 12 entry and 12 exit interviews, observations of three face-to-face meetings of blended learning sessions and ten classroom observations of teachers implementing new teaching approaches learned through blended learning. Findings - The paper provides insights into the authors' experiences in this research. They shared the following reflections: engagement in ID empowered them and they are confident that they can engage in systematic instructional design on a larger scale; they gained technical knowledge and skills in authoring content in HTML on eXe open source platform; uploading the content and processing audio and video content was equally enthralling to them. Research limitations/implications - Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to consider incorporating the design-based research, instructional design and blended learning approaches used in this study while conducting related research in their dissimilar contexts. Practical implications - The paper includes implications for the design, development and implementation of teachers' professional development for challenging contexts as a contribution towards achievement of both Millennium Development Goals (MDGs) and Education for All (EFA). Originality/value - This paper fulfils an identified need to study provision of professional development for teachers who lack opportunities for professional development.
Place: Limerick Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1430572667?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/ejtd-10-2012-0052 2339240:C7CEXRWM 2339240:XN53EQR3 2405685:AFTT7Q76 2405685:UYED6EDY 2405685:ZZ7VUU4G 2534378:32ICX4DB 2534378:UTXP2X7Q
Keywords: 5220:Information technology management; 8306:Schools and educational services; 9177:Africa; Appropriate technology; Audio recordings; Business And Economics–Management; Instructional design; Kenya; Personal development; Professional development; Research; Rural schools; Teaching; Technological change; Training; __:import:01; __:match:final; __:matched; __:study_id:2096396; ___working_potential_duplicate; __finaldtb

A Comparative Study of Online and Directly Selected Secondary School Teachers Regarding Teaching Proficiency and Classroom Management in Kohat Division, Pakistan - Suleman, Qaiser; Hussain, Ishtiaq (International Journal of Learning and Development, 2013)
Secondary school teachers occupy the most critical and crucial position in the entire education system (Suleman, et al, 2011a). The purpose of the study was to compare the performance of online and directly selected secondary school teachers regarding teaching proficiency and classroom Management. All the students at secondary school level in Kohat Division, Khyber Pakhtunkhwa (Pakistan) constituted the population of the study. Only 600 students studying at secondary school level in Kohat Division were selected as sample randomly. The study was delimited to only male students at secondary school level. The study was descriptive type and questionnaire was used as research instrument. Data was collected through personal visits. After the collection of data, it was organized, tabulated, analyzed and interpreted. The statistical tools i.e. means, standard deviation and differences of means were computed for each variable. Significance of difference between the mean values of the responses of students about online and directlly selected secondary school teachers were tested at 0.05 levels by applying t-test. After statisitcal analysis of the data, the researchers conclduded that the overall performance of the directly selected secondary school teachers was better and satisfactory. They were found to have the knowledge of teaching methods and the ability to control classroom disruptive behaviour. Conversely, the overall performance of the online selected secondary school teachers was poor and unsatisfactory. They have no knowledge of teaching methodologies and subject mastery. They were found unable to manage classroom disruptive behaviour and other related activities. Based on findings, it was strongly recommended that a special professional training programme should be arranged to the existing online selected SSTs in teaching methodologies and classroom management to equip them with the modern teaching methods and techniques of managing classroom behaviour so that they become able to perform their duties effectively.
Number: 3 KerkoCite.ItemAlsoKnownAs: 10.5296/ijld.v3i3.4130 2339240:MKBAFBWM 2405685:856AQDD2

Measuring Effectiveness of Mobile Application in Learning Basic Mathematical Concepts Using Sign Language - Parvez, Komal; Khan, Muzafar; Iqbal, Javed; Tahir, Muhammad; Alghamdi, Ahmed; Alqarni, Mohammed; Alzaidi, Amer Awad; Javaid, Nadeem (2019)
Technology plays an important role in our society, especially in the ﬁeld of education. It is quite regrettable that people, particularly the deaf, still face a lot of challenges in acquiring an education. Their learning methods are different as compared to hearing people. They use Sign Language (SL) rather than natural language to communicate and learn. They are required to put a lot of effort into learning different concepts using conventional pedagogies. Therefore, there is a dire need for some assistive technology to improve their learn-ability and understandability. In the present study, 192 deaf participants aged 5–10 years were sampled from two special child institutes. The objective of the present study was to determine the effectiveness of a mobile interface through a developed mobile application for learning basic mathematical concepts using Pakistan Sign Language (PSL). The present study bridges the gap between the technology-based method and conventional teaching methods, which are used for teaching mathematical concepts using PSL. The participants were divided into two groups, that is, one group learned through conventional methods (ﬂash cards and board) and the other group through the developed mobile application. The difference in the performance of both the groups was evaluated by conducting quizzes. The quiz results were analyzed by the Z-test and ANOVA. The ﬁndings revealed that the Experimental Group (EG) participants, who were instructed by our mobile application showed higher proﬁciency in the quizzes as compared to the Control Group (CG). EG participants performed better than CG by 12% in the quizzes. A gender based difference was also observed for the quiz scores. Male participants in category C (word problem learning) performed 2.7% better than females in the EG and 2.5% better in the CG. Moreover, a signiﬁcant difference was also observed in the time taken by participants in both groups to complete the quizzes. CG participants took 20 min longer than EG participants to complete the quizzes. The results of the ANOVA showed that the quiz scores were directly affected by the mode of teaching used for participants in both groups.
KerkoCite.ItemAlsoKnownAs: 10.3390/su11113064 2339240:PJGV4NQP 2405685:A5XR2HFD

Empowering Teachers to Promote Inclusive Education. A case study of approaches to training and support for inclusive teacher practice - Donnelly, Verity (European Agency for Special Needs and Inclusive Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:WMMVHIHD 2405685:ERPJWFQ4

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Universal Design for Learning: Theory and Practice - Meyer, A; Rose, D; Gordon, D (Center for Applied Special Technology., 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:E35ITZ2D 2405685:ZR5RX227

Use of Information communication technology in teaching and learning processes in secondary schools in Rachuonyo South District, Homa-Bay County, Kenya - Obonyo, Samson O. (University of Nairobi, 2013)
The purpose of this study was to investigate the use of Information Communication Technology (ICT) in teaching and Learning in Rachuonyo South District secondary schools. The focus was on three main subject matters: on ICT use and competence, on teacher and student and on ICT infrastructure and teaching practices. The study is closely connected to the national educational policy, which has aimed strongly at supporting the implementation of ICT in pedagogical practices at all institutional levels. Six research questions were formulated to guide the researcher investigate the phenomena. A descriptive survey design was used to collect data from the field through the use of questionnaire and an observation schedule. The result indicated that ICT has not been successfully integrated in teaching and learning in schools. In general, students are capable and motivated users of computers. Some students have the skills to use new kinds of applications and their ICT skills are wider although not necessarily adequate. Teachers’ skills are more heterogeneous. The large majority of teachers have sufficient skills for everyday and routine working practices, but many of them still have difficulties in finding a meaningful integration of ICT into teaching and learning. Most teachers reported that the use of ICT in learning and teaching was slow in the past years and proposed upgrading of students computer labs and accelerating internet connectivity in the schools. Further, teachers’ good ICT competence helps them to adopt new pedagogical practices and integrate ICT in a meaningful way. The results also showed that students are capable and motivated users of new technology and their ICT skills are wide, although not necessarily adequate; the working habit might be ineffective and wrong. Some students have a special kind of ICT related adaptive expertise, which develops in a beneficial interaction between students and teachers, and individual interest and activity. The most common goal to student use of ICT is challenged by the internet, digital communication and the need to filter information. Since students’ ICT skills can be translated to increased creativity, which include innovation and productive workforce, to develop capacity to ICT which support the country’s knowledge base. The findings further indicated that ICT integration realized some challenges such as availability of sufficient number of ICT tools, lack of motivation and support and lack of technical support. The challenges are either teacher-level (Microlevel), school level (Meso-level) or system level (Macro-level). These barriers have hindered successful implementation of ICT into teaching and learning processes. The study also recommended that teachers should be given sufficient training on how to use ICT tools to enhance teaching and learning in schools. The study also recommended that students should be equipped with ICT skills such as Microsoft software applications such as word, excel and access. Finally, further research on the perception of teachers and students towards the use of ICT in enhancing teaching and learning and relevant strategies for using ICT to improve teaching and learning practices should be conducted.
Accepted: 2013-09-13T12:53:42Z KerkoCite.ItemAlsoKnownAs: 2339240:VMGJH5RH 2405685:K3FR5Q2D

Entry, engagement and empowerment: Dilemmas for inclusive education in an Indian context. - Singal, N; Florian, L (The Sage Handbook of Special Education, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:6ZNPUAW5 2405685:BQE39QTV

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Instructional and assessment accommodations in the 21st century. - Thurlow, M (The SAGE Handbook of Special Education: Two Volume Set., 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:HHLQ7XS4 2405685:QCATQYFU

Cost-Effectiveness and Affordability of Interventions, Policies, and Platforms for the Prevention and Treatment of Mental, Neurological, and Substance Use Disorders - Levin, Carol; Chisholm, Dan (Mental, Neurological, and Substance Use Disorders: Disease Control Priorities, 2016)
Since the turn of the millennium, considerable progress has been made in developing an evidence base on which interventions are effective and feasible for improving mental health in low- and middle-income countries (LMICs). Such evidence provides a critical input to the formulation of plans and priorities to address the large and growing burden of mental, neurological, and substance use (MNS) disorders. However, for successful and sustainable scale-up of effective interventions and innovative service delivery strategies, decision makers require not only evidence of an intervention’s impact on health and other outcomes, such as equity or poverty, but also evidence of its cost and cost-effectiveness. Cost data provide information relevant to the financial planning and implementation of prioritized, evidence-based strategies; cost-effectiveness analysis indicates the relative efficiency or value for money associated with interventions or innovations. The application of economic evaluation to MNS disorders has largely focused on the assessment of a specific intervention’s costs and health outcomes, relative to some comparator, which may be treatment as usual, another innovation, or no intervention. Such assessments have often been conducted alongside clinical trials, enabling health economic researchers to add resource use questions to study protocols, generate estimates of each trial participant’s health care costs, and relate these costs to primary outcome measures in the form of cost-effectiveness ratios. We review this type of economic evidence over the course of this chapter, with a particular focus on studies that have been successfully carried out in LMICs. However, the number of completed studies remains small and insufficient to inform resource allocation decisions in all the national settings where cost-effectiveness information would be valuable, including the many countries where informal or traditional health care represents the predominant model of service availability. This paucity of economic evidence reflects the overall lack of resources and infrastructure for mental health services in LMICs, including research capacity. Partly to address the paucity of cost-effectiveness trials, as well as their intrinsic specificity to the setting in which they are conducted, a broader, modeling-based approach has also been used to build up economic evidence for international mental health policy and planning. This approach includes the earlier editions of the Disease Control Priorities (DCP) project and the World Health Organization’s (WHO) CHOosing Interventions that are Cost-Effective (CHOICE) project. Such model-based studies rely on existing data, as well as several analytical assumptions; these studies have adopted an epidemiological, population-based approach that identifies the expected costs and health impacts of delivering evidence-based interventions at scale in the population as a whole, whether a specific country or an entire region. We also review this form of economic evidence and comment on important gaps in the current evidence base, as well as the relative strengths and limitations of this approach. One important limitation of conventional cost-effectiveness analysis—whether garnered through trial-based or model-based approaches—is that it is restricted to consideration of the specific implementation costs and health-related outcomes of an intervention; it does not typically extend to the nonhealth or wider economic or social value of investing in mental health innovation and service scale-up. In particular, cost-effectiveness analysis in its conventional form has little to say about the equitable distribution of costs and health gains across different groups of the target population. Incorporation of such concerns into economic evaluation represents a major objective of extended cost-effectiveness analysis, which is explored and addressed specifically in chapter 13 in this volume (Chisholm, Johansson, and others 2015). In this chapter, we review the available cost-effectiveness evidence for the different levels and underpinning strategies of the mental health care system, with a focus on information generated in or for LMICs. Based on the overall analytical framework and priority intervention matrices developed for this volume, the remainder of the chapter is presented as follows. First, we consider the economic evidence for mental health prevention and protection at the population and community levels of the health and welfare system, including legislative, regulatory, and informational measures at the public policy level (population platform), as well as school-, workplace-, and community-based programs (community platform). We then examine the economic evidence relating to the identification and treatment of MNS disorders (health care platform), focusing on the relative cost-effectiveness or efficiency of treatment programs implemented in nonspecialized versus more specialized health care settings. Finally, we assess the financial costs and budgetary implications of implementing or scaling up a set of prioritized, cost-effective interventions. Our review is based on available, published literature. A systematic search of the literature for LMICs was undertaken in PubMed to find articles published since 2000 in English. The search combined terms for specific mental health interventions with economic terms such as “cost,” “cost-effectiveness,” or “quality-adjusted life year (QALY),” as well as the names of all LMICs and their respective regions (see annex 12A for a list of search terms used to identify relevant literature). Where little or no literature was found for LMICs on interventions of potential importance, this systematic search was augmented by selective searches of the literature available since 1995 for high-income countries (HICs); however, these results are not included in the figures or tables. Annex 12B provides the search statistics. Articles included in the review were graded using the checklist of Drummond and others (2005) to generate a quality score for each article, with most studies graded between 7 and 10. Annex 12C provides a list of studies that were used to generate the tables and figures presented in this chapter. It presents detailed information on the intervention characteristics and comparators, target population group, geographic location, methodology, results, and quality scores. All cost-effectiveness results are presented in 2012 US$ except where noted otherwise. Consistent with earlier iterations of DCP, reported regional estimates refer to the World Bank’s categorization of countries by income.
KerkoCite.ItemAlsoKnownAs: 2339240:MMWPL7JY 2405685:NEXA5KQM

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found